Pengembangan LKPD Cerita Hikayat Bermuatan Toleransi Siswa Kelas X SMA - Muliza; Deliani; Ratna Soraya (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
This study aims to describe the product in the form of saga story worksheets containing tolerance for class X high school students, to describe the validation of saga story worksheets to instill tolerance values ??in students according to material and design experts for class X high school students, to describe the feasibility of validating saga story worksheets to instill Tolerance values ??for students according to material and design experts for grade X high school students. The research method is used as a reference in conducting research. With the research method, the author will have no difficulty determining how to carry out a research because there are already rules that are regulated based on what method is used. In this study, the author uses a 4D research and development method adapted from Thiagajaran. In the assessment of material experts the total score obtained in the first stage of validation was 94 with an average score of 4.47 indicating the "very valid" category, while in the second stage of validation with the table the total score obtained was 78 with an average score of 3.71 indicating the "Valid" category. Thus the results obtained from material experts show the "VALID" category, which means the product is feasible and can be used.